IGSF11 and VISTA: a pair of promising immune checkpoints in tumor immunotherapy - Xi-Yang Tang; Yan-Lu Xiong; Xian-Gui Shi; Ya-Bo Zhao; An-Ping Shi; Kai-Fu Zheng; Yu-Jian Liu; Tao Jiang; Nan Ma; Jin-Bo Zhao (BMC, 2022)
Abstract Immunotherapy has become the major treatment for tumors in clinical practice, but some intractable problems such as the low response rate and high rates of immune-related adverse events still hinder the progress of tumor immunotherapy. Hence, it is essential to explore additional immunotherapy treatment targets. In this review, we focus on the structure, expression and expression-related mechanisms, interactions, biological functions and the progress in preclinical/clinical research of IGSF11 and VISTA in tumors. We cover the progress in recent research with this pair of immune checkpoints in tumor immune regulation, proliferation, immune resistance and predictive prognosis. Both IGSF11 and VISTA are highly expressed in tumors and are modulated by various factors. They co-participate in the functional regulation of immune cells and the inhibition of cytokine production. Besides, in the downregulation of IGSF11 and VISTA, both inhibit the growth of some tumors. Preclinical and clinical trials all emphasize the predictive role of IGSF11 and VISTA in the prognosis of tumors, and that the predictive role of the same gene varies from tumor to tumor. At present, further research is proving the enormous potential of IGSF11 and VISTA in tumors, and especially the role of VISTA in tumor immune resistance. This may prove to be a breakthrough to solve the current clinical immune resistance, and most importantly, since research has focused on VISTA but less on IGSF11, IGSF11 may be the next candidate for tumor immunotherapy.